Epistemology of Arabic Language Learning Technology Development - Nurcholis, Ahmad; Nuryani, Nuryani; Efendi, Heri; Hidayatullah, Syaikhu Ihsan (Universitas Islam Negeri Raden Intan Lampung, 2021)
Students' lack of Arabic language skills might be caused by some factors, such as the models and strategies used by teachers, the students’ excitement in learning and their character. This study aimed to research on the epistemology of Arabic learning based on ICT. It was designed to find the Arabic learning model based on ICT. It assumed that integrating various fields of study with ICT, including Arabic language learning, is essential to be developed in this digital era. However, there are obstacles experienced by several schools, especially the teachers, they do not have a specific format for using ICT to integrate both scientific subjects. Descriptive qualitative research was used in this research. The data collection was done through observation, interviewing the teachers and one hundred X grade students, and documentation. The data were analyzed by using the Miles and Huberman technique. The results showed that the design of the ICT-based in Arabic learning model development is “al-hasub al-ittishalî”, this is an innovative Arabic learning model based on ICT. In this model, the materials and other learning tools are designed in a computer program. As stated by E. L. Criswell, computers provide opportunities for students to participate and respond to the student’s activities actively. This model contributes in making the teaching and learning process more effective. With this model, the teacher is expectedly able to become a learning motivator and a mediator to explain some materials to the students. Besides, the use of ICT is a must considering the digital era.